A Systematic Review of Diuretics in the Medical Management of Ménière's Disease. (1st March 2016) - Crowson, Matthew G.; Patki, Aniruddha; Tucci, Debara L.
Abstract : Objective: (1) Review evidence for the use of oral diuretic medications in the management of Ménière's disease. (2) Analyze therapy‐related hearing and vertigo outcomes. Data Sources: Literature was obtained through directed searches of MEDLINE, EMBASE, Web of Science, EBSCO Host, Cochrane Reviews, and linked citations through seminal papers. We searched independent electronic databases for articles that reported the use of diuretics in patients with Ménière's disease. Review Methods: All articles of level 4 evidence or higher, per the Oxford Centre for Evidence‐Based Medicine, were included with no limit for number of patients, duration of therapy, or follow‐up period. Two independent investigators reviewed the articles for inclusion eligibility. Outcomes were tabulated, including subjective or quantitative measures of hearing, tinnitus, vertigo episode frequency, and medication adverse effects. Results: Nineteen articles were included from 1962 to 2012 from 11 countries. Twelve retrospective case series, 4 randomized controlled trials, 2 case‐control trials, and 1 prospective case series were identified. Six studies investigated isosorbide; 5, hydrochlorothiazide; 2, acetazolamide; 2, chlorthalidone; and 1 each of betahistine, hydrochlorothiazide, chlorthalidone, acetazolamide, hydrochlorothiazide‐triamterene, and nimodipine. Eight (42.1%) studies reported hearing outcomes improvement. Fifteen (79.0%) studies reported vertigo outcomes improvement. Ten (52.6%) studies reported no side effects, and 4 studies (21.1%) reported abdominal discomfort. No significant morbidity or mortality was reported in any study. Conclusion: Multiple low evidence–level studies report that oral diuretic therapy may be beneficial in the medical management of Ménière's disease. Improvement in vertigo episode frequency was consistently reported, with less convincing evidence for improvement in hearing outcomes.